2005
DOI: 10.1126/science.1109727
|View full text |Cite
|
Sign up to set email alerts
|

The Brain of LB1, Homo floresiensis

Abstract: The brain of Homo floresiensis was assessed by comparing a virtual endocast from the type specimen (LB1) with endocasts from great apes, Homo erectus, Homo sapiens, a human pygmy, a human microcephalic, specimen number Sts 5 (Australopithecus africanus), and specimen number WT 17000 (Paranthropus aethiopicus). Morphometric, allometric, and shape data indicate that LB1 is not a microcephalic or pygmy. LB1's brain/body size ratio scales like that of an australopithecine, but its endocast shape resembles that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
198
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(213 citation statements)
references
References 16 publications
12
198
0
3
Order By: Relevance
“…In fact, the volume of the virtual endocast subsequently reported for LB1 by Falk et al (2005a) is appreciably larger, at 417 cc. The discrepancy of 37 cc between these two reported values for cranial capacity, almost 10%, is disconcertingly large.…”
Section: Cranial Capacitymentioning
confidence: 85%
See 3 more Smart Citations
“…In fact, the volume of the virtual endocast subsequently reported for LB1 by Falk et al (2005a) is appreciably larger, at 417 cc. The discrepancy of 37 cc between these two reported values for cranial capacity, almost 10%, is disconcertingly large.…”
Section: Cranial Capacitymentioning
confidence: 85%
“…Indeed, because of the small cranial height associated with the small brain size of this individual, stated that their inferred stature of 106 cm was likely to be an overestimation. Despite this very small cranial capacity, a follow-up study of a virtual endocast derived from the LB1 skull concluded that the brain shows a number of similarities to that of Homo and is closest to that of Homo erectus (Falk et al, 2005a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cranial endocasts allow the observation of some of the external features of the brain. The information on circulatory and nervous system of the endocranium as well as general shapes and volumes can be inferred from endocasts, and such information has been used to address the paleoneurology of fossil hominins (Connolly, 1950;Holloway, 1974;Holloway, 1983;Holloway and Kimbel, 1986;Bruner et al, 2003;Holloway et al, 2004a;Falk et al, 2005;Bruner and Manzi, 2008). Among the most commonly described features of the brain hemispheres are the petalia asymmetries (protrusions of the hemispheres producing imprints on the inner skull surface); the Yakovlenian torque (a forward ''torquing'' of the structures surrounding the right Sylvian fissure relative to their counterparts on the left); and the asymmetry on the occipital horns of the lateral ventricles (a deeper projection on the left occipital bone is common; Toga and Thompson, 2003).…”
Section: Endocastmentioning
confidence: 99%